PENGARUH STRUKTUR AKTIVA DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PT KIMIA FARMA TBK - Rahmi, Hidayatur; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to partially and simultaneously examine the influence of Asset Structure and Capital Structure on Profitability at PT Kimia Farma Tbk. In this study theindependent variable is the Asset Structure and Capital Structure and the dependent variable is Profitability. This study uses secondary data in the form of PT Kimia Farma Tbk financial statements for the period 2011-2018. Data analysis in this study used simple linear regression, multiple linear regression, t test, f test and coefficient of determination using the SPSS 16 program. The results of the analysis show that the Asset Structure variable partially (t test) affects the Profitability, the Capital Structure variable influences the Profitability. Simultaneous test results (f test) showed the influence of the Asset Structure and Capital Structure on the Profitability of PT Kimia Farma Tbk.Keywords: Asset Structure, Capital Structure, Profitability